2022
DOI: 10.31729/jnma.7230
|View full text |Cite
|
Sign up to set email alerts
|

Median Nerve Passing below the Ulnar Head of Pronator Teres in Cadavers of a Medical College in Western Nepal: A Descriptive Cross-sectional Study

Abstract: Introduction: Median nerve passes between two heads of pronator teres muscle while passing through the elbow. Detailed knowledge of these variations in the course of Median Nerve in relation to pronator teres and its neighboring structure is required for diagnosis of pronator syndrome. The aim of the study is to find out the proportion of Median Nerve passing below the ulnar head of pronator teres in cadavers of a medical college in Western Nepal. Methods: A descriptive cross-sectional study was carried out at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Ghosh et al [ 12 ] reported anomalies of three roots (one from medial and two from lateral), four roots (one from medial and three from lateral), and another four roots (one from medial, one from lateral, and two from posterior). Sharma et al [ 13 ] reported the median nerve passing below the ulnar head of the pronator teres in 7.40% of their upper limb subjects, while a normal path between the two heads were seen in the other 92.60%. Caetano et al [ 14 ] reported similar median nerve variation below pronator teres muscle in 3.48% of their subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Ghosh et al [ 12 ] reported anomalies of three roots (one from medial and two from lateral), four roots (one from medial and three from lateral), and another four roots (one from medial, one from lateral, and two from posterior). Sharma et al [ 13 ] reported the median nerve passing below the ulnar head of the pronator teres in 7.40% of their upper limb subjects, while a normal path between the two heads were seen in the other 92.60%. Caetano et al [ 14 ] reported similar median nerve variation below pronator teres muscle in 3.48% of their subjects.…”
Section: Discussionmentioning
confidence: 99%